The Value of Chinese Version GAD-7 and PHQ-9 to Screen Anxiety and Depression in Chinese Outpatients with Atypical Chest Pain - Lin Q; Bonkano O; Wu K; Liu Q; Ali Ibrahim T; Liu L (Dove Medical Press, 2021)
Qiuzhen Lin,1– 4 Ousseina Bonkano,1– 5 Keke Wu,1– 4 Qiming Liu,1– 4 Toure Ali Ibrahim,5 Ling Liu1– 4 1Department of Cardiovascular Medicine, The Second Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Research Institute of Blood Lipid and Atherosclerosis, Central South University, Changsha, People’s Republic of China; 3Modern Cardiovascular Disease Clinical Technology Research Center of Hunan Province, Changsha, People’s Republic of China; 4Cardiovascular Disease Research Center of Hunan Province, Changsha, Hunan, 410011, People’s Republic of China; 5Department of Cardiovascular and Internal Medicine Niger, Niamey Amirou Boubacar Diallo National Hospital, Abdou Moumouni University, Niamey, NigerCorrespondence: Ling LiuDepartment of Cardiovascular Medicine, The Second Xiangya Hospital, Central South University, #139 Middle Renmin Road, Changsha, Hunan, 410011, People’s Republic of ChinaFax +86-73185295407Email feliuling@csu.edu.cnBackground: Atypical chest pain in some outpatients could derive from mental disorders. It is necessary for them to have a preliminary emotional assessment in the outpatient department of Cardiology before psychiatric outpatient visits.Methods: This study included 122 Chinese outpatients with atypical chest pain in the department of Cardiology. They accepted routine examinations, including treadmill test, and were judged by the three-question method as highly likely to have emotional disorders. Then, a standard questionnaire package containing the Chinese version of the seven-item scale for General Anxiety Disorder (GAD-7), Self-rating Anxiety Scale (SAS), the nine-item Patient Health Questionnaire (PHQ-9) and Self-rating Depression Scale (SDS) was administered to evaluate anxiety and depression.Results: The percentages of anxiety evaluated by GAD-7 and SAS were 62.3% and 26.2%, respectively. Analogously, the assessment by PHQ-9 showed a significantly higher percentage of depression than that by SDS (61.5% vs 29.5%) (P < 0.05). Kappa analysis showed that the consistency between GAD-7 and SAS, or that between PHQ-9 and SDS was not very good. About 73% outpatients suffered from emotional disorders, presenting as anxiety/depression evaluated by GAD-7 and PHQ-9. Furthermore, sleep disorders accounted for more than 80% of patients with mental disorders. Finally, the suicidal tendency of depression patients was about 17% that should not be ignored.Conclusion: Compared with SAS and SDS, GAD-7 and PHQ-9 detected more participants with emotional disorders in the Chinese outpatients with atypical chest pain, indicating that GAD-7 and PHQ-9 could be briefly well-validated tools to screen emotional disorders in the outpatient department of Cardiology before psychiatric visits.Keywords: depression, anxiety, screen, atypical chest pain